Mangupura sebagai Ibu Kota Kabupaten Badung: Suatu Penelusuran Historis dan Pengembangan Wilayah - Suwitha, I Putu Gede (Jurnal Kajian Bali (Journal of Bali Studies), 2013)
Abstract This study analysis the new capital city of Badung after Denpasar was decided to be the capital city of the government of Denpasar. Where should the location of the new capital city of Badung? and what is the name of the city? The city must fulfil the condition of a new capital city according to the theoretical frame works that exist so far. This city should alsobe in cooperation with the former city of Denpasar which has already become metropolitan city. This research was done using historical method. The data collection was done through library research and field work in analyzing the problems. Theories and concepts about cities were used.
Keywords: Badung, Mangupura, urbanization, city state, residence, non agraries